Does the built environment matter for active travel among older adults: Insights from Chiba City, Japan. (May 2022) - Yang, Yongjiang; Sasaki, Kuniaki; Cheng, Long; Tao, Sui
Abstract: Demographic ageing in most countries around the world is significant. Japan, the most ageing country in the world, is expected to reach an ageing rate of over 40% by 2055. A better understanding of the daily mobility patterns of older people is fundamental for an ageing society to meet the needs of their daily life. Active travel (cycling and walking) is recognised to deliver a positive effect on physical and mental health, as well as fulfil daily necessities for older people. Most of the existing studies are based on investigation from Western countries' contexts, as well as younger generations. The situation of older adults in the Japanese backgrounds remains largely unknown. As such, this study aims to explore the determinants of older adults' walking and cycling behaviour with a particular focus on built environment factors. A suite of regression models is constructed to analyse active travel frequency and duration in relation to a suite of built environment characteristics respectively. The results show that built environment factors have profound effects on walking and cycling patterns. Specifically, older people are significantly sensitive to the availability of transit facilities, such as the number of bus stops, and distance to the nearest rail transport station. In addition, higher population density and mixed land use contribute to higher walking frequency and duration, while having a negative effect on cycling frequency and duration. These findings provide evidence for policymakers to develop effective land use strategies, public transport provision implications, and public facility distribution to promote older adults' active travel for the Japanese hyper-ageing society.